DESIGN AND SIMULATION VERIFICATION OF METRO ENERGY ABSORBED STRUCTURE BASED ON ASME RT-2 STANDARD (MT) - LIU ZhaoXin; LI YongKuan; XIA DongWei (Jixie qiangdu)
In order to ensure the secondary part at the front end of vehicles absorb the impact energy as much as possible in case of collision, reduce the impact on main parts, and ensure the safety of passengers and drivers, the energy absorption structure is set at the front end of the vehicle to improve the passive safety. Firstly, compared different standards at home and abroad and their requirements for collision conditions. Secondly, ASME RT-2 standard is selected as the standard, two energy absorbing structures are designed respectively. Structures mainly include head girders, corner posts and crash elements. The result shows that both structures can absorb more than 1.22 MJ of energy through the simulation by Ls-Dyna. At last, energy absorbing structures which has two energy absorb stages is tested to verify the reliability of the simulation results, and it is proved that the structure can meet the requirements of ASME RT-2.